Association between elevated cystatin C levels and obstructive sleep apnea hypopnea syndrome: a systematic review and updated meta-analysis - Nianying Fu; Xiaotao Tan; Jie He (BMC Pulmonary Medicine)
Abstract Objective This study seeks to elucidate variances in cystatin C levels between patients with Obstructive Sleep Apnea Hypopnea Syndrome (OSAHS) and controls while also assessing the impact of cystatin C on cardiovascular and cerebrovascular complications in patients with OSAHS. Furthermore, the benefits of surgery or continuous positive airway pressure (CPAP) treatment in reducing cystatin C levels in patients with OSAHS were explored. Methods A thorough search was undertaken across various medical databases, namely PubMed, CNKI, EMBASE, Web of Science, and WanFang, until October 1, 2024, to determine published articles pertinent to OSAHS. The present research conducted a comprehensive review of the literature concerning cystatin C levels in both patients with OSAHS and controls, variations in cystatin C levels pre-and post-surgery/CPAP treatment, the Pearson/Spearman correlation coefficients between cystatin C levels and sleep monitoring indices, and the hazard ratio (HR) associated with cystatin C levels concerning the onset of cardiovascular and cerebrovascular diseases among patients with OSAHS. Meta-analyses were executed utilizing standardized mean difference (SMD) and correlation coefficients (COR) as effect variables. A fixed-effect model was utilized in cases where heterogeneity was not significant (I 2  < 50%). Otherwise, a random-effect model was employed. Statistical analysis was executed utilizing STATA 11.0, GraphPad Prism 8, and R 4.1.3. Results Forty articles were included in the final analysis. The serum/plasma cystatin C levels in the OSAHS group were significantly increased relative to the controls (SMD = 0.65, 95%CI: 0.50–0.79, P < 0.001). Subgroup analysis considering mean body mass index (BMI), mean age, ethnicity, and study design type consistently showed significantly elevated serum/plasma cystatin C levels in the OSAHS category relative to the controls. CPAP treatment can significantly decrease serum/plasma cystatin C levels in patients with OSAHS. Moreover, the increase in cystatin C levels may serve as a risk factor for stroke and MACC in patients with OSAHS. Serum/plasma cystatin C levels exhibited a positive correlation with AHI scores and ODI. Conclusion Elevated cystatin C levels in patients with OSAHS may pose a risk for the onset of cardiovascular and cerebrovascular diseases. Furthermore, cystatin C levels could serve as a valuable clinical indicator for evaluating treatment effectiveness and severity of OSAHS. Clinical trial number Not applicable.